MODEL PENDIDIKAN KESEJAHTERAAN KELUARGA BAGI KELUARGA MISKIN DI PEDESAAN - Kuswardinah, Asih; Ansori, Muhammad; Rosidah, Rosidah (Jurnal Penelitian Pendidikan, 2014)
Development model of study aimed to describe: level of identifying the meaning of welfare family; determinant of welfare family; needs analysis for poor family through FGD. The result of FGD then would be the foundation of planning the textbook and education model for poor family in village area. The subject of this study was 61 poor families in Wonosobo by the particular consideration of local government.The result of the study showed that the level of understanding the family welfare for poor family was Good with the percentage of 18.4%; Average of 52.0%; Fair of 20.9%; Poor of 8.7%. The determinants of family welfare based on the highest mean score for each indicator were: Praying (mean=3.48); Children Education (mean=3.30); Husband-wife communication (mean=3.16); The major determinant was prayer. On the other hand, the textbook material refer to the result of FGD such as: the identification of education and family welfare; interrelationship in the family; parentâs role in educating the children; family financial control; safety and health plan. From the result of the study, it is suggested that Local Government provide both formal and informal education facilities for poor family; Increase the quantity of teaching learning process and workshop especially for creative food processing to poor family. For poor family in village area, it is suggested that they have to improve their knowledge about family welfare.